Sensitivity study on some parameters in blank design - Oliveira, M. C. (2008)
Sensitivity study on various numerical parameters is necessary for modeling a process. It is important to determine the influence of such parameters in order to achieve robust design. Initial blank shape is a process parameter that controls the quality of a formed part. This paper describes a blank shape optimization procedure that uses three numerical tools to determine an optimal blank shape for a formed part. Several numerical parameters that affect the optimization procedure for a deep drawn rectangular cup are analyzed. The focus is mainly on the influence of numerical parameters concerned with the use of NURBS surface in the optimization procedure. From the study, it is evident that the blank shape optimization procedure is sensitive to those numerical parameters. A significant influence of element size and optimization damping factor on achieving optimal blank shape is observed. The number of control points in the NURBS surface and the initial geometry have marginal influence on the optimization procedure.